HUBUNGAN ANTARA POLINOMIAL JONES (ASPEK NON-PERTURBATIF) DAN VACUUM EXPECTATION VALUE DARI OPERATOR WILSON LOOP (ASPEK PERTURBATIF) DENGAN MENGGUNAKAN AKSI CHERN SIMONS WITTEN - Frangki Leko; Asep Yoyo Wardaya (Youngster Physics Journal, 2012)
Perturbatif aspect of Chern Simons Witten theory is viewed as value of Vacuum Expectation Value (VEV) of Wilson loop operator while non-perturbatif aspect of Chern Simons Witten theory is viewed as value of Jones Polynomial. Both aspects will be compared. Calculation of Jones Polynomial is counted by using braiding formula concept which later will be applicated to (SU)2 gauge group. VEV calculation of Wilson loop operator is counted by using Feynman’s diagram and by using vertex and propagator values. Both calculations will be counted to second order of coupling constant. The result of this research indicate that value of pertubatif aspect and non-perturbatif aspect is same although both aspects was counted by two different methods. Keyword : Chern Simons Witten, Vacuum Expectation Value, Wilson loop, Jones Polynomial.